ARTIFICIAL INTELLIGENCE IN ACCOUNTING: TECHNOLOGICAL INNOVATION, PROFESSIONAL TRANSFORMATION, AND HUMAN–AI INTERACTION - Amelia Rizky Alamanda, (Journal of Innovation Research and Knowledge, 2026)
Artificial Intelligence (AI) is rapidly reshaping the accounting profession, yet research in this domain remains fragmented across technical, organizational, and behavioral perspectives. This study provides a structured synthesis of AI-related accounting research by integrating bibliometric analysis and qualitative content analysis. Using research articles indexed in Scopus between 2017 and 2026, keyword co-occurrence mapping was conducted using VOSviewer, followed by in-depth thematic examination of representative studies aligned with identified clusters. The findings reveal three dominant research streams: (1) analytical and predictive applications of AI, emphasizing machine learning and decision-support systems; (2) professional and organizational transformation, focusing on digital transformation, governance, and role reconfiguration; and (3) education and human–AI interaction, driven by generative AI and large language models. Overlay visualization further demonstrates a temporal evolution from AI as computational infrastructure toward AI as an interactive collaborator embedded within professional and educational contexts. The study shows that AI augments rather than replaces accounting professionals, while trust, transparency, and capability development emerge as critical determinants of sustainable integration. By combining structural mapping with theory-driven synthesis, this review advances a multilevel sociotechnical understanding of AI in accounting and proposes a research agenda to guide future inquiry